FORMULASI KRIM EKSTRAK ETANOL BETATAS UNGU (Ipomoea batatas L.) - Sulistianingsih Sulistianingsih; Ravika Ramli; Herlando Sinaga (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
This research aims to determine the best formulation from the cream of a purple sweet potato (Ipomoea batatas L.) ethanol extract. This type of research is descriptive with a laboratory experimental approach. Samples of purple sweet potato (Ipomoea batatas L.) used were from Arso 3 Keerom Regency. The extraction method used is the maceration method using 70% ethanol solvent. In this research, ethanol extract of purple sweet potato was made a cream with three formulas using variations of stearate acid concentration, namely: F1-6%, F2-12%, and F3-18%. The cream will be evaluated including the organoleptic test, pH test, a homogeneity test, irritation test, accelerated stability test. The results showed that the best cream formulation for ethanol extract of purple sweet potato was F3 with variations in stearate acid concentration (18%). Cream F3 has a purplish red color, has a distinctive odor, thick, homogeneous consistency, pH 7, and does not change after storage for ± 3 weeks.